Histopathological Changes in Placenta in Pre-Eclampsia/Eclampsia: A Case-Control Study in A Tertiary Care Center - Choudhary, Prabesh Kumar; Baral, Reetu; Nepal, Niraj; Bhandari, Rashmita; Shrestha, Oshan; Choudhary, Sarita; Dhakal, Hari (Journal of Nobel Medical College, 2025)
Background: Hypertensive disorders of pregnancy, particularly pre-eclampsia and eclampsia, remain major causes of maternal and perinatal morbidity and mortality. The placenta plays a pivotal role in their pathogenesis, with histopathological lesions correlating with adverse outcomes. This study was therefore conducted to compare various placental gross and histopathological changes in hypertensive disorders of pregnancy as compared to normotensive pregnancy. Materials and Methods: A case-control study was conducted on 28 placentas from pre-eclamptic/eclamptic pregnancies and 28 from normotensive controls at Nobel Medical College (Sep 2024–Feb 2025). Birth weight in both groups was compared. Various gross and histological features like placental weight, umbilical cord length, insertion of placenta, infarction, calcification, chorioamnionitis, villitis, placental dysmaturity, chorionic vessel thrombosis, and subchorioinic fibrin deposition were assessed and compared. Data were analyzed using appropriate statistical tests. Results: Placental weight and neonatal birth weight were significantly lower in hypertensive pregnancies (p=0.0001 and p=0.018, respectively). Histopathological lesions—such as calcification, infarction, subchorionic fibrin deposition, chorionic vessel thrombosis, and chorioamnionitis—were significantly more frequent in hypertensive cases (p<0.05 for each). Conclusion: Significant gross and microscopic placental changes are associated with hypertensive disorders of pregnancy. Routine placental histopathology can aid in understanding disease mechanisms.